Adaptive Diversification in the Cellular Circadian Behavior of Arabidopsis Leaf- and Root-Derived Cells. (22nd January 2022) - Nakamura, Shunji; Oyama, Tokitaka
Abstract: The plant circadian system is based on self-sustained cellular oscillations and is utilized to adapt to daily and seasonal environmental changes. The cellular circadian clocks in the above- and belowground plant organs are subjected to diverse local environments. Individual cellular clocks are affected by other cells/tissues in plants, and the intrinsic circadian properties of individual cells remain to be elucidated. In this study, we monitored bioluminescence circadian rhythms of individual protoplast-derived cells from leaves and roots of a CCA1::LUC Arabidopsis transgenic plant. We analyzed the circadian properties of the leaf- and root-derived cells and demonstrated that the cells with no physical contact with other cells harbor a genuine circadian clock with ∼24-h periodicity, entrainability and temperature compensation of the period. The stability of rhythm was dependent on the cell density. High cell density resulted in an improved circadian rhythm of leaf-derived cells while this effect was observed irrespective of the phase relation between cellular rhythms. Quantitative and statistical analyses for individual cellular bioluminescence rhythms revealed a difference in amplitude and precision of light/dark entrainment between the leaf- and root-derived cells. Circadian systems in the leaves and roots are diversified to adapt to their local environments at the cellular level.